Application of light shelves in a refurbished student dormitory: Energy, lightings and comfort aspects. (September 2021) - Assimakopoulos, Margarita-Niki; De Masi, Rosa Francesca; de Rossi, Filippo; Ferrante, Annarita; Fotopoulou, Anastasia; Papadaki, Dimitra; Ruggiero, Silvia; Vanoli, Giuseppe Peter
Abstract: The transparent elements of the building envelope have a crucial role not only in term of heat and mass transfers control, but also for natural light penetration, sound insulation, thermal and visual comfort of the occupants and their health. Among passive technologies, the light shelves could be architectural solutions for improving daylight penetration and for controlling thermal loads. The available research papers usually focus on one aspect. For this reason, the aim of the present study is to analyse the application of the light shelves with multidisciplinary approach and thus, taking into account: daylight, electricity for lighting, cooling and heating needs and thermo-hygrometric comfort. The case study is a real dormitory building placed in Athens and subject to a deep energy renovation toward the nearly zero energy building target. EnergyPlus, by means of DesignBuilder interface, has been used as dynamic simulation tool. Among ten different configurations, the optimal one turns out to be the internal horizontal light shelf placed at 50 cm from the top of the window with a depth of 90 cm or 60 cm. It has been found that in some cases the reduction of electricity for lighting cannot balance the variation in heating and cooling needs.